1994
DOI: 10.1128/mcb.14.10.6647
|View full text |Cite
|
Sign up to set email alerts
|

The 64-kilodalton subunit of the CstF polyadenylation factor binds to pre-mRNAs downstream of the cleavage site and influences cleavage site location.

Abstract: The CstF polyadenylation factor is a multisubunit complex required for efficient cleavage and polyadenylation of pre-mRNAs. Using an RNase H-mediated mapping technique, we show that the 64-kDa subunit of CstF can be photo cross-linked to pre-mRNAs at U-rich regions located downstream of the cleavage site of the simian virus 40 late and adenovirus L3 pre-mRNAs. This positional specificity of cross-linking is a consequence of CstF interaction with the polyadenylation complex, since the 64-kDa protein by itself i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
197
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(205 citation statements)
references
References 35 publications
8
197
0
Order By: Relevance
“…The nucleotide sequence surrounding the cleavage site is not strictly conserved [51,52]. In vertebrate pre-mRNAs, 70% of the cleavage sites are located at the 3′ side of an adenosine residue [53], with a nucleotide preference of A > U > C ≫ G. The nucleotide preceding the cleavage site is cytosine in 59% of 269 pre-mRNA sequences examined [53], making the optimal cleavage site CA (Fig.…”
Section: The Downstream Element (Dse)-mentioning
confidence: 99%
“…The nucleotide sequence surrounding the cleavage site is not strictly conserved [51,52]. In vertebrate pre-mRNAs, 70% of the cleavage sites are located at the 3′ side of an adenosine residue [53], with a nucleotide preference of A > U > C ≫ G. The nucleotide preceding the cleavage site is cytosine in 59% of 269 pre-mRNA sequences examined [53], making the optimal cleavage site CA (Fig.…”
Section: The Downstream Element (Dse)-mentioning
confidence: 99%
“…However, subsequent experiments demonstrated that p64 was in contact with the GU-or U-rich downstream element (8), an interaction stabilized by CPSF acting at the AAUAAA site (39,40). The Rna15 subunit of yeast CF IA, whose ribonucleoprotein-type RNA binding domain closely ressembles that of CstF p64 (41), can be cross-linked to polyadenylation substrate, but this interaction does not show a sequence dependence like that of Cft2 (22).…”
Section: Table Imentioning
confidence: 99%
“…4). The largest subunit (160 kDa) of CPSF binds specifically to the AAUAAA signal located upstream of the poly(A) site (6,7), and the CstF binds to the GUor U-rich downstream element via its 64-kDa subunit (8).…”
mentioning
confidence: 99%
“…CstF-77 bridges the other two subunits of the complex (21). CstF-64 is responsible for the binding of CstF to RNA (12), as it interacts through a ribonucleoprotein-type RNA binding domain with the U͞GU-rich element downstream of poly(A) sites. CstF-77 and CstF-50 interact with the carboxyl-terminal domain of RNA polymerase II (14).…”
mentioning
confidence: 99%
“…Assembly of the cleavage complex on the pre-mRNA results from multiple RNA-protein and protein-protein interactions. CPSF binds to a highly conserved AAUAAA element (11), the polyadenylation signal, located upstream of the cleavage site, whereas CstF recognizes a U͞GU-rich element (12), located downstream of the cleavage site. Binding of CPSF and CstF to the pre-mRNA is cooperative and allows the recognition of the poly(A) site.…”
mentioning
confidence: 99%